2002
DOI: 10.2133/dmpk.17.457
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Structurally Novel, Serial Diglucuronide of 4-Hydroxybiphenyl by Further Glucuronidation of a Monoglucuronide in Dog Liver Microsomes

Abstract: Incubation of 4-hydroxybiphenyl (p-phenylphenol) in the presence of UDP-glucuronic acid (UDPGA) with liver microsomes from male and female dogs produced a more polar metabolite peak than a simultaneously produced peak of 4-hydroxybiphenyl monoglucuronide in the high performance liquid chromatography (HPLC) chromatogram. Tandem mass spectrometry (MS/MS) and two-dimensional nuclear magnetic resonance (NMR) analyses revealed this polar metabolite as a 4-hydroxybiphenyl diglucuronide having a beta-D-glucuronopyran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…4), which is common among the diglucuronides characterized previously (Dixon et al, 1989;Murai et al, 2002Murai et al, , 2005Murai et al, , and 2007). The hydroxyl group at the C2Ј position of the glucuronosyl group in a specific monoglucuronide was recognized as a functional group for further glucuronidation by unique dog UGT isoforms, which would have similar enzymatic properties to human UGT1A8, as demonstrated in our previous study in vitro (Murai et al, 2006).…”
Section: Identification Of Steroid Hormone Diglucuronide In Vivo In Dogsmentioning
confidence: 74%
See 1 more Smart Citation
“…4), which is common among the diglucuronides characterized previously (Dixon et al, 1989;Murai et al, 2002Murai et al, , 2005Murai et al, , and 2007). The hydroxyl group at the C2Ј position of the glucuronosyl group in a specific monoglucuronide was recognized as a functional group for further glucuronidation by unique dog UGT isoforms, which would have similar enzymatic properties to human UGT1A8, as demonstrated in our previous study in vitro (Murai et al, 2006).…”
Section: Identification Of Steroid Hormone Diglucuronide In Vivo In Dogsmentioning
confidence: 74%
“…After the discovery of nalmefene diglucuronide, we reported that diglucuronides could be produced in vitro from 4-hydroxybiphenyl, a phenolic compound used commonly as a model substrate for glucuronidation (Murai et al, 2002). Moreover, we found that endogenous sex steroids, namely androsterone, dihydrotestosterone (DHT), estradiol, estriol, estrone, and testosterone, also undergo diglucuronidation in vitro (Murai et al, 2005).…”
mentioning
confidence: 99%
“…Pooled rat liver microsomes were also obtained from BD Gentest. Dog liver microsomes used were prepared as described previously (Murai et al, 2002). All microsomes were stored frozen at approximately Ϫ80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…After the discovery of nalmefene diglucuronide in vivo, we were the first to report the in vitro production of the diglucuronide of 4-hydroxybiphenyl, a nonplanar phenolic compound used commonly as a model substrate for glucuronidation, using dog liver microsomes (Murai et al, 2002). The diglucuronidation reaction was found to proceed in a stepwise manner, from 4-hydroxybiphenyl to 4-hydroxybiphenyl monoglucuronide and from the monoglucuronide to the diglucuronide.…”
mentioning
confidence: 99%
See 1 more Smart Citation